CHARACTERIZATION OF COAL SEAMS IN THE ARANTIGA AND SELUANG MINE BENGKULU USING PROXIMATE ANALYSIS DATA - Rafi Maulana; Ordas Dewanto; A Raka Abriyansyah (Engineering Faculty Universitas Lampung, 2020)
Indonesia as a country that has ample large coal reserves spread across the Sumatera and Kalimantan islands. The huge potential in the region needs further research to be able to find out the quality and excellence of coal resources in order to know the characteristics in detail, then the research was carried out in the Bengkulu Province area by testing coal sample based on Proximate analysis to obtain accurate coal quality results and analysis of coal characteristics in the area can be carried out. The results show that the coal seams in the Arantiga mine have an average value Inherent Moisture is worth 7.49 %, ASH is worth 9.82 %, Volatile Matter is worth 40.99 %, Fixed Carbon is worth 41.70 %, Total Sulfur is worth 0.34 %, Gross Caloric Value is worth 6305 kcal/kg and including of High Volatile A Bituminous coal type, while the Seluang mine has an average value Inherent Moisture is worth 2.07 %, ASH is worth 22.92 %, Volatile Matter is worth 20.26 %, Fixed Carbon is worth 54.78 %, Total Sulfur is worth 0.55 %, Gross Caloric Value is worth 6365 kcal/kg dan and including of Medium Volatile Bituminous coal type.